PENGARUH SURFACE ACTING TERHADAP KETIDAKHADIRAN DENGAN SURFACE ACTING SELF-EFFICACY SEBAGAI VARIABEL PEMODERASI PADA PERAWAT RUMAH SAKIT UMUM CUT NYAK DHIEN DIKOTA MEULABOH - Irhamna Putri, Fairuzzabadi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
Abstrack :This study aims to determine the effect of surface acting to absenteeism with surface acting self-efficacy as a moderating. The empirical study conducted at Cut Nyak Dhien Hospital's nurse used a questionnaire as a research instrument, which samples in this study of 148 people. Probability sampling is used as a sampling technique with Simple Random Smpling. Methods MRA (Moderated Regression Analysis) is used as a method of data analysis using IBM SPSS software 22. These results indicate that the surface acting positive and significant impact on absenteeism, surface acting self-efficacy positive and significant to absenteeism, and in addition showed that the surface acting self-efficacy moderate negatively effect of surface acting to absenteeism.